Manual de procesos para la comercialización fob (puesto a bordo), del cacao (theobroma cacao l.), en la asociación fortaleza del valle ubicada en la ciudad de Calceta. - Cedeño German, Juan Carlos (2011)
This research aims the design of the Marketing Process Manual FOB at the Strength Valley Association, and approach the problem in its manufacture. It is a feasible project, based on the field and documentary research.The research population was formed by employees of the Administrative Area of the Association and guests, the sample is given by the Administrative employees and customers that are related to the activities taking place in the FOB market, four employees and five clients. To obtain data we proceeded to use two techniques and the survey interview, the type of questionnaire that was submitted to the validation process through the trial of an expert and consisted of eleven items for the Management Area and eleven items for customers, the results were tabulated and qualified according to the responses given by subjects of study. Subsequently did not found any manual process for the marketing of cocoa fob that allows full compliance with the effectiveness and efficiency in marketing activities FOB; As we proceeded to perform the lifting of the processes, then we designed the manual process taking into consider, responsibilities and functions that meet each employee, once made and checked the manual proceeded to socialization, recommending the immediate implementation to improve organizational quality and service.